IN ISCHEMIC HEART DISEASES UNUSUAL COMPLAINTS - Aslanov G A.; Boʼronov Batir Boyir son; Rustamov J. I. (Web of Journals Publishing, 2024)
This article provides information on ischemic heart disease, causes, symptoms, and measures
Keywords: Heart diseases, myocardial ischemia, atherosclerosis, angina pectoris, stroke, heart attack.